PENGARUH KOMPENSASI DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI DINAS PERTANIAN TANAMAN PANGAN HOLTIKULTURA DAN PETERNAKAN KABUPATEN PASAMAN BARAT - Yurasti Yurasti (Jurnal Apresiasi Ekonomi, 2017)
The purpose of this study was to determine the influence of Compensation and Job Satisfaction toward Employee Performance at the Department of Agriculture Horticulture and Animal Husbandry in West Pasaman. The population in this study were all contract employees in that place with sample size about 31 people, where sampling techniques using saturated sampling. The research instrument was a questionnaire. Thus, the data collection processed using multiple linear regression analysis with SPSS. From the result of this study found variable Compensation (X1) and Job Satisfaction (X2) on the Performance (Y) about 0,481 (R2 = 48.1). Keywords : Compensation, Job Satisfaction, Performance